Tornar-se filho na perspectiva de crianças adotadas tardiamente - Araujo, Ivy Campista Campanha de (2017)
In spite of the importance of reciprocity in the creation of a bond between parents and their respective children, late adoption goes on with the prioritization of the adult’s discourse in Brazil; in a way that the feelings and the wants of the infant are usually put on the background of the adoption process. Besides what is hereby stated, it is noticeable that the ongoing search for adoption of tender-aged children reveals the petitioners’ apprehensions on adopting older children. One of the arguments to defend these concerns is the fact that bigger children carry a history from their previous family, and that this experience could hinder the bonding process in the new family. Facing these considerations, this presented work has as an objective the investigation of facilitating and challenging aspects on the filial process constitution in a family that resorted to a late adoption, privileging the children’s perspective on the new family interaction. The family elected by this research is compound by a couple, a man and a woman at the age group of forty years old, who took part of the late adoption process of a group of four siblings. The three oldest children, of ages five, eight and ten, were involved in the research along with the couple. Six meetings took place in the family’s house in the aims of data collection; these moments relied on interviews with semi-structured scripts, genogram elaboration and observation throughout procedures along with the registration on the field journal. Parents have described challenges on the adaptation process: family and marital routine reorganization, dissatisfactions with couple’s tasks division on the mother’s side, need to make bigger investments on the two oldest children when it comes to school learning and meeting the demands of the four children at once. However, none of these comes across as a difficulty on the process of becoming a son/daughter. The executed interventions reveal that the adoption was mutual and ongoing, being that both the children and the parents were experiencing the emotions of a parental/filial bond. The children mentioned daily scenes illustrating the feeling of being taken care of, corrected and supported by the parents, highlighting more familiarity towards the mother. The proximal processes using objects and symbols, all present on the three children’s familiar microsystem, also favored the development of their feeling of belonging and filiation to the family, for they both called the attention for their place in this new environment and reinforced the preoccupation and the affection towards them and from the members of the family. It is possible to reckon that the research brings the expansion of information on late adoption, contributing for the knowledge about the topic. In addition, it was made clear that the policies of post-adoption monitoring could help the experience of challenges presented by families that resort to late adoption, especially in the case of those who adopt a group of siblings.